THE EFFECT OF COOP FERTILIZER (COW FESES) AND PLANT DISTANCE ON THE GROWTH AND YEAR OF GREEN BEANS: (Pengaruh Dosis Pupuk Kandang (Feses Sapi) Dan Jarak Tanam Terhadap Pertumbuhan dan Hasil Tanaman Kacang Hijau) - Assagaf, Said Abdurrahman; Utomo, Yasser (Uniqbu Journal of Exact Sciences, 2021)
Mung bean is a short-lived annual plant of approximately 60 days, also acts as a tropical plant which throughout its life requires a hot atmosphere, which means that when in an area with low rainfall levels it is ideal if cultivating mung bean plants, the purpose of this study is to see the effect. Dose of Manure (Cow Feces) and Plant Distance on Growth and Yield of Mung Bean (Vigna Radiata L) in Batuboy Village). This research was conducted in Batuboy village, Namlea District, Buru Regency, and lasted from December 2016 to February 2017. The experiment’s purpose was to determine and analyze the response of manure (cow feces) and spacing to the growth and yield of green bean plants. The experiment used a randomized block design (RBD) with a factorial pattern consisting of 2 factors, namely the provision of manure dose (first factor) and use of spacing (second factor). The first factor has three levels, namely K0 (without treatment), K1 (fertilizer dose of 1000 kg / h), K2 (fertilizer dose of 2000 kg / h). The second factor, the spacing consisted of 3 levels, namely J1 (50 x 10 cm), J2 (50 x 20 cm), J3 (50 x 30 cm), thus obtaining 9 treatments / combinations with 3 replications / group so that there were 27 units / units. trial. This study indicates that the application of manure (cow feces) 2000 kg/ha has a good effect on the growth and yield of green beans compared to others. This can be seen from the weight of production/plot 3.03 kg, while the best combination treatment is produced by a combination of 180 gr/plot manure and 50 x 30 cm spacing (K2J3).